The Making of Southeast Asia international relations of a region - Amitav Acharya (Cornell University Press; Revised ed, 2013)
Developing a framework to study "what makes a region," Amitav Acharya investigates the origins and evolution of Southeast Asian regionalism and international relations. He views the Association of Southeast Asian Nations (ASEAN) "from the bottom up" as not only a U.S.-inspired ally in the Cold War struggle against communism but also an organization that reflects indigenous traditions. Although Acharya deploys the notion of "imagined community" to examine the changes, especially since the Cold War, in the significance of ASEAN dealings for a regional identity, he insists that "imagination" is itself not a neutral but rather a culturally variable concept. The regional imagination in Southeast Asia imagines a community of nations different from NAFTA or NATO, the OAU, or the European Union.